Research static hardness of the compressed alder wood - Chopenko , Nataliya (Forestry, Forest, Paper and Woodworking Industry, 2024)
Influencing of compressing on static butt hardness of alder wood have been researched. A mathematical model is got. A mathematical model describes dependence static butt hardness from initial density and compressing measures.